The Relevance of Positive Education Concept for Pesantren in Indonesia - Moh Maqbul Mawardi; Fida Ruhiyah (The Faculty of Tarbiyah and Teacher Training associated with PSPII, 2022)
Studies on positive education that integrates traditional education with happiness and well-being is increasing rapidly. Unlike previous studies that were conducted in context of the Western world, the study aims to examine the relevance of special positive education to the education system in Indonesia particularly at pesantren. The research uses a qualitative approach with a case study design examining the concept of positive education offered by Seligman and its relevance to the education system at pesantren. The results show that the positive education program was designed at pesantren to teach well-being and achievement. Its implementation consists of several stages: teaching, embedding, and living positive education. The education system at pesantren is carried out in a curriculum namely the academic curriculum and the hidden curriculum. The hidden curriculum becomes a medium for transformation of santri character, values, morals, resilience, and the meaning of life based on religious values. There is a relevance relationship between the education system offered in positive education and the education system applied at pesantren. Pesantren in fact have implemented the principles offered by positive education although they have not taught specifically in one material about well-being, happiness and resilience as programmed in the implementation of positive education.